Textbook of Radiographic Positioning and Related Anatomy - Bontrager, Kenneth L.; Lampignano, John P. (St. Louis, Mo. : Mosby, 2014)
"This radiography text focuses on the most commonly performed radiographic exams as determined by an extensive survey. To help students better visualize and understand positioning, this text features one projection per page and a "show-and-tell" style that lines up explanation of the featured projection with positioning photos, radiographic images and anatomy line drawings.
This outstanding fifth edition includes an all new full color design, new information on pathology, geriatric and pediatric patient populations, expanded survey information, and 100 new positioning photographs for the latest in radiographic positioning."--BOOK JACKET.
(3SjO GdJhfSj (B/ (3cJH cdjI GdYdhe GdWHjIs
Includes bibliographical references and index.
Keywords: Radiography, Medical -- Positioning; Human anatomy; Technology, Radiologic; Anatomy